Human Papillomavirus associated prevention: knowledge, attitudes, and perceived risks among men who have sex with men and transgender women in Pakistan: a qualitative study - Muslima Ejaz; Anna Mia Ekström; Alyan Ahmed; Aymen Haroon; Dania Ali; Tazeen Saeed Ali; Mariano Salazar (BMC, 2022)
Abstract Objectives Men who have sex with men (MSM) and transgender individuals are at higher risk of genital warts and anal cancer due to sexually transmitted human papillomavirus infection. This study explores MSM and transgender women's perceptions of Human papillomavirus (HPV) infection and HPV prevention strategies (screening and vaccination) in Pakistan. Design A qualitative study using focus group discussions (FGD) with self-identified MSM, male sex workers and transgender women were conducted between March 2019 to August 2019 in Karachi, Pakistan. Methods Participants were recruited from community-based organization (CBO) working for MSM and transgender women. A total of 38 men and 10 transgender women took part in 6 FGDs. Discussions were recorded, translated, transcribed verbatim and analyzed using content analysis. Results Three themes were identified from the emerging analysis. These are, 1) Knowledge and risk perceptions about STIs and HPV, 2) Beliefs and attitudes towards HPV prevention, 3) Participant's recommendations for HPV vaccination and anal Pap screening. Participants described lack of knowledge of HPV and its health consequences as HIV is the only focus of attention of the government and the local CBOs. None of participants had heard about HPV prevention including vaccination and anal Pap screening for men but expressed a positive attitude towards prevention. Genital warts and anal cancer were perceived as severe potential consequences of a known risk behaviors. All participants stated they would be interested in taking an HPV vaccine but acknowledged that the provision of services for sexually transmitted infections (STI) are inadequate to meet the needs of key populations and are not prioritized by the government. The main perceived barriers to access HPV prevention included cost and challenges to access public health care services or openly discussing one's sexual orientation with health care providers. Participants generally preferred the CBO for more professional, unbiased staff attitudes that respect patients' integrity, confidentiality and privacy. Most participants thought that in case the government is non-cooperative, CBOs should work in the interest of HPV eradication and generate funds through international funding. Conclusions The findings from this study can help public health policy and researchers to understand this minority's perspective on HPV prevention. Given the low level of knowledge about HPV infection and its negative health consequences there is a need of HPV education combined with STI education and awareness through HPV brochures to educate the target population effectively.